Técnicas deglutorias en pacientes adultos mayores con disfagia orofaríngea. - Calero Sánchez, Mariuxi Jeseña (2025)
Oropharyngeal dysphagia is a noticeable change in the safety and effectiveness of moving solid and liquid food from the mouth to the stomach. Physiotherapeutic interventions, particularly through swallowing techniques, can optimize swallowing function and improve the quality of life for older adults. This study aims to evaluate the effects of these swallowing techniques as a physiotherapeutic treatment for oropharyngeal dysphagia in older people, to enhance their quality of life and autonomy. An extensive bibliographic review was conducted, utilizing scientific articles from databases such as PEDro, PubMed, Elsevier, and the Cochrane Library. In total, 65 articles were identified, and after assessment using the PEDro scale, 25 randomized controlled clinical trials were selected for analysis. The results indicated several positive effects: improvements in swallowing function, increased orofacial muscle strength, and a reduced rate of hospitalizations and complications caused by aspiration pneumonia, dehydration, and malnutrition. The findings also highlighted the importance of integrating additional techniques that yield positive results in swallowing function, ultimately enhancing older adults' quality of life and autonomy. Implementing swallowing techniques significantly improves the functionality of older adults experiencing oropharyngeal dysphagia. It helps prevent complications such as aspiration pneumonia and reduces the risks of malnutrition and dehydration. This, in turn, leads to fewer hospitalizations and a decreased mortality rate in this vulnerable population.